Performance optimisation of parabolic trough solar thermal power plants – a case study in Bangladesh. Issue 2 (7th February 2020) - Bhuiyan, Noushad; Ullah, Wali; Islam, Rabiul; Ahmed, Tofael; Mohammad, Nur
ABSTRACT: In this paper, parabolic trough solar thermal plants are proposed. Two key parameters, solar multiple (SM) and full load hours of thermal energy storage (TES), are optimised by maximising the annual energy and minimising the levelized cost of electricity (LCOE). This work presents a comparative study, based on the 4E (energy–exergy–environment–economic) analysis, of the optimised plant with a reference plant. The performance evaluation of the optimised plant is carried out in eight different locations of Bangladesh. The result obtained shows that the salt plant has the best performance compared to that of the thermal oil plant. The salt plant requires a lower LCOE of 9.86 ¢/kWh. It also possesses a maximum capacity factor of 39.5% and generates the highest annual energy of 171.1 GWh. From the feasibility study, Cox's Bazar is found as the best location of eight different regions of Bangladesh.